2016
DOI: 10.1007/s11295-016-0968-0
|View full text |Cite
|
Sign up to set email alerts
|

The plastome sequence of the endemic Amazonian conifer, Retrophyllum piresii (Silba) C.N.Page, reveals different recombination events and plastome isoforms

Abstract: Retrophyllum piresii (Podocarpaceae) is an endemic conifer species from the Brazilian Amazonian Region, and very few data related to ecological and genetic characteristics of this species are available. Plastome sequencing is an efficient tool to understand enigmatic and basal phylogenetic relationships at different taxonomic levels, as well as to probe the structural and functional evolution of plants. Usually, the plastome of photosynthetic land plants is quadripartite, with two copies of the inverted repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 62 publications
(119 reference statements)
0
13
0
Order By: Relevance
“…2011 ), whereas other studies of conifers suggested a repeat-mediated homologous recombination mechanism based on a circular unit genome ( Guo et al. 2014 ; do Nascimento Vieira et al. 2016 ; Hsu et al.…”
Section: Discussionmentioning
confidence: 99%
“…2011 ), whereas other studies of conifers suggested a repeat-mediated homologous recombination mechanism based on a circular unit genome ( Guo et al. 2014 ; do Nascimento Vieira et al. 2016 ; Hsu et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Sciadopitys contains specific IRs (called rpoC2 -IRs) that are proven to be re-combinable 7 . The trnN -IRs that were proposed to be responsible for formation of isomeric plastomes 8 are common in Podocarpaceae 51 . All three Araucariaceae genera possess rrn5 -IRs, though their recombinant activity has not been assessed 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Plastome sequences are also of great importance to understand evolutionary events in plants based on the knowledge of gene content, recombination events, loss of genes, gene transfer to the nucleus and genome rearrangements (Vieira et al 2016b;Bock 2017;Lopes et al 2017;Park et al 2017;Ruhlman et al 2017), as well as for plastid transformation aiming basic research (Rogalski et al 2006(Rogalski et al , 2008Alkatib et al 2012) and biotechnological applications (Daniell et al 2016;Zhang et al 2017) since the complete sequence of plastome is a prerequisite to choose target intergenic regions for insertion of transgenes and development of transplastomic plants (Daniell et al 2016;Fuentes et al 2017). The plastid transformation has been used efficiently for metabolic engineering (Daniell et al 2016;Fuentes et al 2017) and it is a viable alternative to manipulate plastid fatty acid biosynthesis (Rogalski and Carrer 2011) given that several efficient protocols of plant regeneration based on somatic embryogenesis are available for macaw palm (Moura et al 2009;Luis and Scherwinski-Pereira 2014;Padilha et al 2015).…”
Section: Introductionmentioning
confidence: 99%